PENGARUH PERMAINAN ULAR TANGGA BERBASIS UNPLUGGED CODING TERHADAP KECERDASAN LOGIKA MATEMATIKA ANAK USIA DINI DI TK AL-HAFIZ KOTA PADANG - Putri Nadiah Irfan; Dadan Suryana (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2026)
The development of the snakes and ladders game based on unplugged coding has a game concept without using technology. Researchers use the snakes and ladders game by collaborating with children's mathematics learning. The purpose of the study was to determine the effect of the snakes and ladders game based on unplugged coding on the logic-mathematical intelligence of 5-6 year olds at Al-Hafiz Kindergarten Padang. The study used a quantitative approach (One Group Pretest-Posttest design). The research sample consisted of 12 children in the Safa group as purposive sampling. The results of the research and discussion show statistical test data, including the normality test reaching 1.586 with a significant value of 0.117, the homogeneity test reaching 0.967-0.975, and the paired sample t-test reaching -7.167 with the highest value of -6.123. Based on the data analysis, the snakes and ladders game based on unplugged coding has an influence on children's mathematical logic abilities with aspects of number recognition, game strategy, counting, patterning, and problem solving in the game. The purposive sampling test on the average pretest value variance of 20.5% increased to 26.5% in the posttest technique. The results of the paired sample t-test showed a significant value of the data in the snakes and ladders game. This can be concluded that the snakes and ladders game has a moral meaning full of challenges. Participants can design a systematic game strategy in completing the game mission. Based on the data, the snakes and ladders game based on unplugged coding has a significant influence on children's logic-mathematical abilities.